KOMITE AUDIT, KUALITAS AUDIT DAN MANAJEMEN LABA (Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2017) - Venny Dwi Lestari; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2019)
This study aims to analyze the interaction between internal and external corporate governance mechanisms in reducing earnings management. The other aims of this research is to analyze the influence of the audit committee and the interaction between the audit committee and the external auditor in reducing earnings management.The characteristic of this research is the audit committees are assessed by forming a score of the number of members forming an audit committee and the number of audit committee meetings in one year, while the audit quality of external auditors is measured based on industry auditor specialization, auditor reputation and auditor tenure. The selection of samples in this study was determined using purposive sampling method to obtained 116 manufacturing companies in Indonesia. Multiple linear regression analysis was used to test the hypothesis of this study.The results of this study indicate that the audit committee does not negatively affect earnings management, the interaction between the audit committee and industry specialist auditors does not affect earnings management, the interaction between the audit committee and the Big Four auditor negatively affects earnings management and the interaction between the audit committee and auditor tenure is not affect earnings management.